Um poeta em exposição: os públicos e a expografia do museu dedicado a Augusto dos Anjos - Leonardo Gonçalves Ferreira; Letícia Julião (Midas: Museus e Estudos Interdisciplinares)
The article analyses the institutionalization of the memory of the poet Augusto dos Anjos (1884-1914), carried out by the Museu Espaço dos Anjos, located in Leopoldina, Minas Gerais (Brazil). The purpose is to understand the effectiveness of the exhibition's narrative in establishing recognition of Augusto dos Anjos and the museum itself as heritage sites of the city. To this end, an analysis of the exhibition was carried out, comparing it to the assumptions that categorise the so-called house museums and/or biographical museums, noting limits on the affinity of the Museu Espaço dos Anjos with these types of museums. Despite narrative gaps and inconsistencies, the lack of a coherent exhibition circuit, built from an objective curatorial conception, it was possible, through a visitor study, to observe that the museum and the poet are heritage references for the residents of Leopoldina. These findings led to infer that the effectiveness of the Museum, in relation to the public, is anchored in the fact that the institution appears as a memory-museum or narrative-museum. Beyond the visitor study and the exhibition analysis, we used documentary research and interviews with actors involved with the museum.